A framework for interpreting in vitro genotoxicity data: Using mechanistic data to interpret positive results - Braun, P.; Fowler, P.; Hendriks, G.; Stoddart, G. (Spanish Journal of Environmental Mutagenesis and Genomics, 2023)
Non-animal methods are increasingly being used for regulatory decision making by agencies worldwide because of their potential to reliably and efficiently produce information that is fit for purpose while reducing animal use. The prediction of genotoxic hazard to humans usually follows a stepwise approach, beginning with an in vitro battery consisting of a gene mutation test in bacteria, an in vitro test for chromosomal damage and/or gene mutation in cultured mammalian cells. Depending on the in vitro test results and regulatory requirements, the in vitro battery may be followed in some cases by in vivo testing. When the standard battery of two or three in vitro genotoxicity tests was retrospectively analysed it was found that a high percentage of in vivo non-genotoxic or rodent non-carcinogenic compounds gave positive results in at least one in vitro test. The in vitro chromosome damage assays gave a high percentage of misleading positive results, often related to choice of cell line and confounded by differing methods of estimating cytotoxicity. To better interpret in vitro genotoxicity results, it has been suggested that all available information including in silico and in vitro data should be considered in a holistic weight of evidence approach. Clarification of the mechanism of action (MoA) of the test chemicals proves particularly valuable for decision-making. This poster presents illustrative case studies showing how MoA assessment using non-animal methods such as the ToxTracker system, as well as other non-animal methods, can provide information on the potential genotoxic mode of action. Examples are presented where results from in vitro genotoxicity tests can be rationalised with a holistic data driven approach, potentially reducing the need for in vivo follow-up testing. Mode of action information allows for a more accurate and concrete assessment of genotoxicity. Investigation of MoA using targeted methods without animal testing has great potential to clarify positive in vitro genotoxicity test results, thereby avoiding in vivo follow-up testing.